Globalization and the Labor Market - Rama, Martín (World Bank, 2013)
Does globalization affects labor market outcomes? Can labor market policies mitigate or offset the effects? Would these polices have important side effect on efficiency this article addresses these questions through an analytical survey of the literature, including several studies under preparation. Some of the studies use new cross-country database of wages and other labor market indicators. Although all the answer should be considered tentative some patterns emerge. Different aspects of globalization have different consequence. In the short run wages fall with openness to trade and rise with foreign direct investment also increase (substantially) the returns to education. Social protection programs are effective in reducing inequality. Minimum wages, public sector employment, and core labor standards are not. Between these two extremes, collective bargain works mainly for the middle class. Social protection programs do not adversely affect efficiency, but high public sector employment and trade union membership are associated with weaker performance in the context of adjustment.